The effect of incremental training intensities on joint dynamics in elite rowers - Buckeridge, E.; Bull, A.; McGregor, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Rowers train at a range of work intensities in order to develop aerobic fitness as well as explosive leg power and strength. Changes in lumbo-pelvic (LP) kinematics have been noted when rowing at higher intensities (McGregor et al., 2004), however, little is known about the changes in joint loading patterns that occur at various work rates. Therefore the aim of this study was to quantify the effects of incremental work rates on lower limb and LP loading during ergometer rowing. Methods: Twelve elite female rowers performed an incremental step test on a rowing ergometer. Each rowed for 3 minutes at the following strokes rates; 18, 24, 28 strokes per minute and free rate (i.e. maximum effort). A motion tracking system recorded 3D kinematic data of rowers` ankle, knee, hip and LP joints. External forces were measured by load cells incorporated at the handle, seat and foot stretchers. Intersegmental joint moments were calculated using inverse dynamics. Changes in joint loading and performance parameters, with respect to work rate, were examined using repeated measures ANOVA. Results: No change in maximum handle force, vertical foot force or horizontal foot force were observed as work rate increased, whilst maximum seat force increased from 11.9 to 13.2 N/kg (p<0.05). All joints exhibited significantly increased extension moments at the catch and increased peak flexion moments during the recovery phase. Peak ankle extension moments increased from 1.16 to 1.22 Nm/kg (p<0.05). There was a small reduction in peak knee extension moment from 3.84 to 3.66 Nm/kg (p<0.05), whilst peak hip extension moments were stable across all rates. Peak LP extension moments increased from 12.55 to 13.11 Nm/kg (p<0.05) and this was coupled by proportional increases in LP flexion and pelvis range of motion (p<0.05). Discussion: Large LP extension moments were present during the rowing stroke and increased with respect to work rate. Flexion moments also increased during recovery, as higher stroke rates meant they had less time to slide naturally into the catch position. There was an increase in the ratio of peak hip to peak knee extension moments, which was due to reduced effort at the knee rather than increased effort at the hip. Consequently, the increase in LP loading at higher work rates is unlikely to be a measure of greater performance, as corresponding increases in handle and foot stretcher forces were not observed. Alternatively, it may be an indicator of technique decline at higher work rates, as larger peak LP extension moments occurred alongside increases in LP flexion and posterior hip range of motion.